Husband's Support in Efforts to Prevent Stunting During Pregnancy at the Akbar Medika Clinic, Mojokerto Regency - Meilinawati SB, Elies; Nurhayati, Nunuk (Kirana Publisher (KNPub), 2024)
Stunting is a disorder of child growth and development, caused by chronic malnutrition and repeated infections that last for a long time, generally from pregnancy to the age of 2 years. Preventing stunting is an important priority, especially during pregnancy. The support of a husband greatly influences the psyche of a pregnant woman to act and make the best decisions to determine her health status. If the husband support the mother to check her pregnancy, maintain a diet, avoid stress, maintain her health and so on, then the mother will be motivated and enthusiastic in undergoing her pregnancy. The purpose of this study was to determine the description of husband's support in preventing stunting during pregnancy at the Akbar Medika Clinic, Mojokerto Regency. The research design used in this study was descriptive. The population was all pregnant women in the third trimester at the Akbar Medika Clinic, Mojokerto Regency, as many as 30 people with the sampling technique used non-probability sampling type of accidental sampling as many as 28 people. The results of this study are that husband's support in efforts to prevent stunting during pregnancy in pregnant women in the third trimester is mostly good (60.7%). The characteristics and sociodemographics of pregnant women's husbands are related to their husbands' support in efforts to prevent stunting during pregnancy, some of which are age and education. The higher the husband's age, the better the knowledge he gets and the better his mindset, so that the husband behaves well, especially in providing support. The higher the level of education of the husband, the better the support given. With higher education, husbands can more easily receive information and are able to apply all things or good behavior for their wife's pregnancy. Keywords: husband support; Efforts to prevent stunting during pregnancy